2020
DOI: 10.3390/ijms21114131
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling Reveals Novel Candidate Genes Related to Hippocampal Dysfunction in SREBP-1c Knockout Mice

Abstract: Lipid homeostasis is an important component of brain function, and its disturbance causes several neurological disorders, such as Huntington’s, Alzheimer’s, and Parkinson’s diseases as well as mood disorders. Sterol regulatory element-binding protein-1c (SREBP-1c) is a key modulatory molecule involved in lipid homeostasis in the central nervous system. However, little is known about the biological effects of SREBP-1c in the brain. Our previous study uncovered that mice deficient in SREBP-1c exhibit schizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…The differentially expressed genes and proteins, suggested as novel molecular candidates related to the hippocampal dysfunction of SREBP-1c KO mice in our previous study, may also provide insights into the neuroplastic alterations found in the current study [ 20 ]. Glp2r , a gene associated with neuroprotection and neurogenesis [ 43 ], and Ndn , a gene associated with neuronal differentiation and survival [ 44 , 45 ] and axonal growth [ 45 ], decrease especially in the CA3 pyramidal cell layers of SREBP-1c KO mice [ 20 ]. Although the proteins have no known direct physical or functional interactions with SREBP-1 based on a protein–protein interaction network analysis [ 20 ], their possible indirect interactions with SREBP-1c and/or other neuroplasticity-related molecules cannot be discounted.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The differentially expressed genes and proteins, suggested as novel molecular candidates related to the hippocampal dysfunction of SREBP-1c KO mice in our previous study, may also provide insights into the neuroplastic alterations found in the current study [ 20 ]. Glp2r , a gene associated with neuroprotection and neurogenesis [ 43 ], and Ndn , a gene associated with neuronal differentiation and survival [ 44 , 45 ] and axonal growth [ 45 ], decrease especially in the CA3 pyramidal cell layers of SREBP-1c KO mice [ 20 ]. Although the proteins have no known direct physical or functional interactions with SREBP-1 based on a protein–protein interaction network analysis [ 20 ], their possible indirect interactions with SREBP-1c and/or other neuroplasticity-related molecules cannot be discounted.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, the remaining SREBP-1 expression present in the hippocampi of SREBP-1c-specific KO mice indirectly represents the remaining proportion of the SREBP-1a isoform in the different subregions. Furthermore, the Srebf-1a mRNA expression significantly increased in the whole hippocampal lysates of SREBP-1c KO mice [ 20 ]. Therefore, SREBP-1a might have played a role in mitigating the SREBP-1c-induced structural alterations by providing an alternative, compensatory pathway for the de novo lipid synthesis, as it shares common functions with the SREBP-1c isoform.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations